Projecting nitrous oxide over the 21st century, uncertainty related to stratospheric loss - Michael J. Prather; Calum P. Wilson (Proceedings of the National Academy of Sciences, 2026)
Extending the N 2 O lifetime derived from Microwave Limb Sounder satellite observations, we find a mean value of 117 y and a likely decrease of –1.4 ± 0.9% per decade over the period 2004 to 2024. This trend is consistent with the previously published 2004 to 2021 value of –2.1 ± 1.2% per decade. A more careful analysis of uncertainty now provides a more robust likely (one-sigma) range. From analyses of a range of factors controlling the N 2 O lifetime, we find that the decrease in lifetime can be explained by recent changes in stratospheric circulation and temperature. Projection of the lifetime change to 2100 shows that this effect is comparable to differences across the shared socioeconomic pathways used for climate projections and cannot be ignored. An updated evaluation of the N 2 O chemical feedbacks shows that this effect produces a relatively small shift in atmospheric abundance over the 21st century, but still an important shift, –11%, in the global warming potential of N 2 O.